Peran Mbah Banjar, Mbah Mayang Madu, Raden Qosim Sunan Drajat Dalam Penyebaran Islam Masyarakat Pesisir Utara Lamongan - M. Muhlis; Nur Iftitahul Husniyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
The spread of Islam in Java, especially the north coast of Lamongan, was inseparable from the efforts of preachers and saints, especially the following figures, Mbah Banjar, Mbah Mayang Madu and Raden Qasim Sunan Drajat, including the main figures who preached Islam in the North Coast of Lamongan, changing what used to be Hindu-Buddhist religion is the largest Muslim majority on the island of Java. By carrying out a distinctive da'wah mission with a cultural approach in accordance with the culture that existed at that time without coercion without conflict. The first started with the preaching of Mbah Banjar in converting Mbah Mayang Madu, who at that time was the ruler of the Jelaq village area. After that brought in Raden Qoshima who finally made rapid developments in the world of education in the area with the existence of Islamic boarding schools as a forum for fostering and developing Islamic religious knowledge. Then after the establishment of the Islamic boarding school as a center for the development of Islamic teachings, Raden Qohim further developed Islamic teachings with a wise and subtle da'wah strategy, he always taught his followers not to hurt each other, live in harmony and peace, also not to be divided. He also utilizes various media in preaching such as Gedning, Gamelan and existing culture as a form of cultivating local culture.